Mechanical characterization of rubberized concrete using an image-processing/XFEM coupled procedure. (1st September 2015) - Duarte, A.P.C.; Silva, B.A.; Silvestre, N.; de Brito, J.; Júlio, E.
Abstract: A coupled (two-step) numerical procedure to characterize the mechanical behaviour of Rubberized Concrete (RuC) is proposed and validated in this paper. In particular, the splitting tensile strength test is described in detail. In the first step, MATLAB Image Processing is used to obtain the model geometry and the RuC heterogeneous configuration (distribution of rubber particles within the concrete matrix). In the second step, the Extended Finite Element Method (XFEM) included in ABAQUS software is used to simulate the inelastic behaviour of the concrete matrix and allow the nucleation and development of cracks, as well as the damage evolution and ultimate strength of the RuC specimen cross-section. Additionally, a set of experimental results on mechanical behaviour of RuC is presented. This shows that RuC has both lower strength and stiffness but higher ductility (less brittle behaviour) than normal concrete (NC). Finally, a good agreement between the two-step procedure results and the experimental results (in terms of indirect tensile strength, stiffness and failure mode) is observed.